POTENSI MASYARAKAT DAN KELEMBAGAAN LOKAL DALAM PEMBERDAYAAN KELUARGA MISKIN DI PERDESAAN (STUDI KASUS KABUPATEN BONE) - Bustang Bustang; Basita G. Sugihen; Margono Slamet; Djoko Susanto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2008)
The aim of the research was intended to formulate the model of poor familiy Empowerement by determining both the level and the influencing factors of social responsibility and level of empowerment. Survey and interview techniques were implemented among 276 selected samples, started Nopember 2006 until April 2007. Data was analyzed by using both correlation and path analysis. The results indicated that a number of respondent had a high social responsibility and medium level of empowerment. The increase of social responsibility and level of empowerment were influenced by implementation of good government of local organization, income, and formal education. This study suggests an alternative model of empowerment in order to social responsibility and level of empowerment.